Dielectric loss reduction and validation of P(VDF-HFP) films via sandwiching film fabrication for capacitive energy storage. (January 2023) - Wu, Xudong; Ivry, Yachin; Zheng, Jiani; Zhang, Pengmiao; Zheng, Zhuojie; Tan, Daniel Q.
Abstract: Poly(vinylidene fluoride) (PVDF) series polymers have a high dielectric constant (k) among polymer families but a high intrinsic loss tangent disqualifying their capacitor application. In this work, Poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) copolymer as the high-k dielectric layer is sandwiched between two low-k polyetherimide (PEI and PEI/BaTiO3 ) layers to construct the composite films with tunable dielectric responses. By changing the low-k layer thickness in the PEI/P(VDF-HFP)/PEI tri-layer structure, its characteristic of capacitors in series results in the moderate dielectric constant and dramatic reduction of loss tangent to a meaningful level for capacitor design. The loss tangent can be dramatically reduced to below 0.005 at 1 kHz using the thickness ratio of 1:1:1 from about 0.03 for P(VDF-HFP) film alone. The extraordinary dielectric response of the tri-layer structure is also accompanied by more than 2 times the higher energy density than that of the PEI film under the same electric field. The ingenious design of the low-k/high-k/low-k sandwiched polymers synergizes the high-k advantage of P(VDF-HFP) and low tangent loss of the low-k layer as well as their high dielectric strength. This work provides a meaningful and effective method for realizing PVDF-based polymers with reduced loss tangent for actual capacitor application. Graphical abstract: Image 1 Highlights: The dielectric constant of the low-k/high-k/low-k sandwiched film is tunable by increasing the low-k layer thickness. The energy storage density of the PEI/P(VDF-HFP)/PEI sandwiched films becomes 2 times higher than that of PEI film. The tri-layer structure can reduce the dielectric loss of lossy P(VDF-HFP) films to 0.005, meaningfully low for capacitor application. The computer simulation reveals the field and polarization distribution in various dielectric thickness ratios.